Common Causes of Leakages in Parapet Roof Construction in Ghana: A Case Study from Kumasi (Journal of Science and Technology, 2016)
In Ghana, especially Kumasi, the second largest city after Accra, the country\'s capital, parapet roof construction became fashionable in building construction in the 1970\'s. It entailed hiding the roofs of buildings from view behind parapet walls. This concept is popularly known as “Bohyemu”, literally meaning “construct it inside\'” or more appropriately “hide it in”. The paper examines roof designs and their functional requirements in general and specifically discusses problems associated with parapet roof construction in the country, with particular reference to Kumasi. It outlines some examples of such roofing and their respective problem areas, which include design and poor detailing, and offers practical suggestions that may help in arresting these problems. The paper concludes by sounding a note of caution to technocrats in the building professionto be more diligent in the detailing, construction and supervision of this type of roof, aswell as “diagnosing” problems of leakages associated with parapet roofs, since they are usually caused by a plethora of factors which, if not well-considered and assessed, may ultimately lead to the wrong “prescriptions” in trying to in solve them.